Pengaruh Kecemasan Sosial terhadap IGD pada Remaja - Arvia Deanna Putri; Lilim Halimah (Bandung Conference Series: Psychology Science, 2022)
Abstract. Online games are form of technological advancement that can provide pleasure for players, but if it is used excessively it will cause serious problems, namely Internet Gaming Disorder (IGD). Many teenagers who experience social anxiety try to relieve their anxiety by playing online games. The long term use and excessively play in online gaming will have a negative consequences on the lives of the players, such as mood disorders, health problems, and reduce individual performance. The purpose of this study was to obtain empirical data related to the effect of social anxiety on Internet Gaming Disorder (IGD) in adolescents. The design of this research is quantitative research with causality method. The sample of this research was 112 teenagers who are actively playing MMORPG type online games in Bandung. The Internet Gaming Disorder Scale (IGDS) constructed by Lemmens, et al. (2015) was used to measure the level of Internet Gaming Disorder (IGD), and the Social Anxiety Scale for Adolescent (SAS-A) constructed by La Greca & Lopez (1998) was used to measure social anxiety. The results of data processing with a simple linear regression analysis showed that social anxiety give influences on Internet Gaming Disorder (IGD) in adolescents, with P value = .000 < 0.05 and a coefficient of determination of .208 or 20.8%. Abstrak. Game online merupakan salah satu bentuk kemajuan teknologi yang dapat memberikan kesenangan bagi pemainnya, namun jika digunakan secara berlebihan maka akan menimbulkan masalah yang serius yaitu Internet Gaming Disorder (IGD). Remaja yg mengalami kecemasan sosial banyak yang berusaha untuk meredakan kecemasannya tersebut pada game online. Penggunaan game online dalam jangka panjang dan secara berlebihan akan menimbulkan dampak negatif dalam kehidupan pemainnya, seperti gangguan mood, gangguan kesehatan, dan menurunkan kinerja individu. Tujuan penelitian ini adalah untuk memperoleh data empiris terkait seberapa besar pengaruh kecemasan sosial terhadap Internet Gaming Disorder (IGD) pada remaja. Desain penelitian ini adalah penelitian kuantitatif dengan metode kausalitas. Sampel penelitian ini sebanyak 112 remaja yang aktif bermain game online jenis MMORPG di Kota Bandung. Alat ukur yang digunakan adalah Internet Gaming Disorder Scale (IGDS) yang disusun oleh Lemmens, et al. (2015) untuk mengukur Internet Gaming Disorder (IGD), dan Social Anxiety Scale for Adolescent (SAS-A) yang disusun oleh La Greca & Lopez (1998) digunakan untuk mengukur kecemasan sosial. Hasil pengolahan data dengan teknik regresi linear sederhana menunjukan adanya pengaruh kecemasan sosial terhadap Internet Gaming Disorder (IGD) pada remaja, dengan nilai P = .000 < 0.05 dan nilai koefisien determinasi sebesar .208 atau 20.8%.